Design and implementation of a high sensitivity differential capacitance sensing circuit for MEMS accelerometers - Estrada, Erik John C. (2009)
MEMS Accelerometers have diverse applications ranging from vehicle deployment systems, industrial process control, vibration monitoring, space launches and inertial measurements. For robotics applications such as tilt measurements, a high sensitivity accelerometer capable of detecting very small G variations are often required to achieve better accuracy in sensor readings. And for the same applications, MEMS capacitive accelerometers are widely used due to several performance and technological advantages. High sensitivity capacitance sensing circuit is implemented for a high sensitivity MEMS accelerometer. This circuit is capable of detecting very small signal variations from the capacitive accelerometer while minimizing noise and parasitics, thus improving the overall sensitivity of the system. This project describes the design and implementation of a high sensitivity differential capacitance sensing circuit (CSC) for interfacing high sensitivity MEMS capacitive accelerometer. The circuit is designed to detect at least 0.1% of the total capacitance change in the accelerometer at full-scale of g-measurement. This would mean a minimum detectable acceleration of about mG or even less when integrated with a suitable accelerometer.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Microelectromechanical systems; Microelectromechanical systems -- Design and construction; Accelerometers; MEMS Accelerometers; Capacitive accelerometer